Digitalna tehnologija v ortotiki in protetiki - Bombek, Matic (Rehabilitacija (Ljubljana), 2019)
Digital technology in the field of orthotics and prosthetics can enable more precise manufacturing, shortening of technological procedures and their simplification. It can be involved in various stages of treatment of the patient and manufacturing of devices (either serially or custom-made). The paper presents the basics of digital technology and its most common use or potential use in the field of orthotics and prosthetics. Examples of using digital technology in the process of manufacturing medical devices at the University Rehabilitation Institute in Ljubljana are also presented.
Keywords: CAD-CAM; digital technology; digitalna tehnologija; manufacturing process; orthosis; Orthotic Devices; ortoze; procez izdelave; prosthesis; proteze